Computed tomography guided fine needle aspiration cytology of mass lesions of lung: our experience in a tertiary care hospital - Mahajan, Vidhu; Sharma, Mansi; Suri, Jyotsna; Atri, Surinder K.; Kalsotra, Nipun (International Journal of Research in Medical Sciences, 2021)
Background: The present study was undertaken to evaluate the diagnostic usefulness of image guided fine needle aspiration cytology (FNAC) in various lung lesions-both neoplastic and non- neoplastic. Method: This retrospective study (Jan 2016-Dec 2018) included 34 cases of lung lesions with strong probable radiological diagnosis of lung neoplasm. Computed tomography (CT)-guided FNAC was performed and cytological smears were stained with May-Grunwald-Gimesa (MGG) stain and conventional Papanicolaou (Pap) stain. Result: A total of 34 cases of lung masses in our study, included 21 males (61.7%) and 13 females (38.2%). The age interval varied from 15 to 85 years; majority presenting in 6th and 7th decade of age. Smears were broadly categorized into unsatisfactory (n=2;5.88%), benign (n=3;8.82%), suspicious of malignancy (n=2;5.88%) and malignant lesions (n=27;79.41%). Benign category included 2 cases of tuberculosis and 1 case of abscess. Malignant category included the cases, diagnosed as squamous cell carcinoma(n=8); poorly differentiated carcinoma (n=6); small cell carcinoma (n=3); adenoma carcinoma (n=2); primitive neuroectodermal tumor (n=2); non-Hodgkins lymphoma (n=2) and plasmacytoma (n=1). Malignant category also included one case each of Metastatic Adenocarcinoma, adenoid cystic carcinoma, renal cell carcinoma with known primary site of Tumours. Conclusions: CT-guided FNAC is a less expensive, simple, fast, relatively safe and accurate procedure in the diagnosis of difficult lung lesions; the major limitation being the adequacy of the aspirate.